Analisis Beban Kerja Sebagai Penentu Jumlah Tenaga Kerja Pemeliharaan Tanaman Tebu di MKSO PT. SGN Rayon Kebun Sei Semayang - Ronaldi Rajagukguk; Prihatin Lumbanraja; Nazaruddin Nazaruddin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze workload as a basis for determining the optimal number of maintenance workers in sugarcane plantations at PT SGN Rayon Kebun Sei Semayang. Facing a decline in productivity and increasing production demands, the company must align the number of workers with actual workload to improve efficiency and effectiveness. The research applies the work sampling method to identify the proportion of time spent on productive, non-productive, and personal activities, and the Full Time Equivalent (FTE) method to categorize workload levels (underload, normal, overload) and determine the ideal number of workers required. Data were collected through direct observation, interviews, and documentation, involving 25 daily maintenance workers as research subjects. The findings are expected to provide empirical evidence for workforce planning based on actual workload conditions and serve as a strategic input for PT SGN’s human resource management. Furthermore, this study contributes to the development of labor management strategies, particularly in the sugarcane agribusiness sector, and offers a reference for optimizing organizational performance by realigning workload distribution and workforce size.